Comparative politics : principles of democracy and democratization - Ishiyama, John T., 1960- (Chichester, West Sussex, U.K. ; Wiley-Blackwell, 2012)
'By revealing the contextual conditions which promote or hinder democratic development, Comparative Politics shows how democracy may not be the best institutional arrangement given a country's unique set of historical, economic, social, cultural and international circumstances. Addresses the contextual conditions which promote or hinder democratic development . Reveals that democracy may not be the best institutional arrangement given a country's unique set of historical, economic, social, cultural and international circumstances. Applies theories and principles relating to the promotion of the development of democracy to the contemporary case studies'--
'How does one promote the development of political democracy? And what are the factors that help explain the emergence of political democracy? By providing the answers to questions like these, Comparative Politics helps shape our understanding of why the'building' of democracy in post-war Iraq remains so elusive -- and reveals that democracy may not, in fact, be the best institutional arrangement given a country's unique set of historical, economic, social, cultural and international circumstances. After examining the historical development of democracy in such cases as Great Britain, France, the U.S., Germany, Russia, and Japan, chapters proceed to address the contextual conditions which promote or hinder democratic development. Choices and elements of the'design' of political systems are then considered, including presidential vs. parliamentary vs.'mixed' systems, legislative and judicial design, and the relationship between military and civilian authorities. With scholarly precision, Comparative Politics offers rich insights into the reasons why there is no universally applicable institutional design that can help'promote' democracy -- along with the impediments that can prevent the fruition of any such design'--
Machine generated contents note: Chapter 1: Introduction -- Comparative Politics and Democracy. -- Chapter 2 The development of democracy in historical perspective. -- Chapter 3 Economic and Political Development. -- Chapter 4: Political Culture and Ethnicity. -- Chapter 5: Social Structure and Civil Society. -- Chapter 6: The Global and International Environment. -- Chapter 7: Electoral Systems. -- Chapter 8: The Structure of the Executive and the Legislature. -- Chapter 9: Comparative Judicial Politics and the territorial arrangement of the political system. -- Chapter 10: Conclusion: Principles in Application.
Includes bibliographical references and index.
Keywords: Comparative government; Democracy; Democratization